THE INFLUENCE OF BMI ON POSTURAL STABILITY OF WOMEN IN THE PERIOD OF EARLY OLD AGE - Grażyna Olchowik; Marek Tomaszewski; Agata Czwalik; Monika Tomaszewska (Rozprawy Społeczne, 2019)
Introduction In this study, a quantitative analysis of the BMI index on the postural stability of women in early old age was conducted.